The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1186/s13071-019-3607-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of Rhipicephalus haemaphysaloides serpin RHS2 on host immune responses

Abstract: Background Rhipicephalus haemaphysaloides is a widespread tick species in China and other South East Asian countries, where it is the vector of many pathogens. The objective of this study was to study the role of serpin (serine protease inhibitor) during the tick-host interaction. Methods The differentiation of bone marrow-derived dendritic cells (BMDC) was induced in vitro , and the effect of RHS2 on the maturation of DCs was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…2009 ; Chmelar et al. 2011 ; Xu et al. 2019 ) or prolong feeding by disrupting hemostatic proteolytic cascades ( Chmelar et al.…”
Section: Resultsmentioning
confidence: 99%
“…2009 ; Chmelar et al. 2011 ; Xu et al. 2019 ) or prolong feeding by disrupting hemostatic proteolytic cascades ( Chmelar et al.…”
Section: Resultsmentioning
confidence: 99%
“…One likely reason for this is that ticks are able to modulate host immune responses. 6,50,51 A recent study by Xu et al 52 showed that a tick serine protease inhibitor suppressed adaptive immune components, including IgG2, and it is conceivable that in guinea pigs, low levels of humoral immunity, in concert with cellular immunity, may be sufficient to induce a cutaneous hypersensitivity response. Passive transfer experiments comparing tick rejection induced by either immune serum or peritoneal exudate cells/lymph node cells have shown that cellular immunity has a greater effect than humoral immunity, although the differences are inconsistent among tick species and, to our knowledge, have not been reported for I. scapularis.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant HL-p36 and RH36 also directly inhibited the proliferation of several mitogen-stimulated cells in vivo and the expression of several cytokines such as IL-2, IL-12, and TNF-α (141,142). In addition to its effect on DCs, RHS2 can prevent the activation of CD4 + and CD8 + T cells, leading to inhibition of the Th1 immune response (132). Two salivary cystatins from I. scapularis, Sialostatin L and Sialostatin L2, have shown promising anti-inflammatory and immunosuppressive activity in vitro and in vivo (141,142).…”
Section: Cell-mediated Immunitymentioning
confidence: 99%
“…PGE 2 has been described as the major DC inhibitor (Figure 3) in both I. scapularis (130) and Amblyomma sculptum saliva (131). RHS2 from Rhipicephalus haemaphysaloides can inhibit the differentiation of BMDCs into DCs in vitro and promote their differentiation into macrophages (132). RHS2 also inhibits the expression of CD80, CD86, and the major histocompatibility complex class II (MHCII), thereby preventing DC maturation.…”
Section: Antigen Processing and Presentationmentioning
confidence: 99%